POTRET KASIH SAYANG IBU DALAM KARYA LUKIS REALIS KONTEMPORER - Drs. Abd. Hafiz, M.Pd., Arif Satriyo Pambudi, Drs. Erfahmi, M.Sn., (Serupa The Journal of Art Education, 2017)
The purpose of the creation of this final work is to visualize the moral values contained in the form of maternal love through the expression of contemporary realist art. The method of creating artwork, using five stages of preparation, elaboration, synthesis, realization of concepts and completion and exhibition. Using acrylic paint on canvas with brushstrokes technique and using colors that match the object. Ten works are made to represent a theme that tells the story of a portrait of mother's love that prioritizes careers and searching for material as much as possible, to forget the duties and obligations to care, nurture, and supervise his children.Keywords: Mother's Love, Painting, Contemporary Realist